Sosialisasi tentang Dampak Bullying pada Remaja - Romadhona Kusuma Yudha; Elfahmi Lubis; Rusnita Hainun; Syarkati Syarkati (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The case of bullying is no stranger to the ears of mass media observers. In television electronic media, broadcasters explain through radio electronic media, and journalists write it down in various newspapers. Often the law and government are not fast and careful in handling bullying cases in Indonesia. Finally, the perpetrators and victims of bullying continue to increase over time. In addition, cultural factors can also encourage someone to do bullying. When we talk about culture, of course we talk about habits. The habit of children who bully (make fun) because he thinks that it is a normal action, and the response given by the victim is the same. Furthermore, the impact of bullying on the behavior of bullies is that most of the subjects interviewed stated that they felt guilty and regretful after they bullied their friends. This is obtained because of the attitude of the bullying victim who tends to be silent and does not respond to the actions of the bullies themselves. The victim also does not avoid the perpetrator, and there is also a small number who do good to the perpetrator